2016
DOI: 10.3390/nu8120807
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fatigue Effects of Small Molecule Oligopeptides Isolated from Panax ginseng C. A. Meyer in Mice

Abstract: Panax ginseng C. A. Meyer (ginseng) is an edible and medicinal Chinese herb, which is often used in Asian countries for physical fitness. Ginseng is reported to have a wide range of biological activity and pharmaceutical properties. There were more studies on ginsenosides and polysaccharides, but fewer studies on ginseng oligopeptides (GOP), which are small molecule oligopeptides isolated from ginseng. The present study was designed to evaluate the anti-fatigue effects of GOP in mice and explore the possible u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(89 citation statements)
references
References 40 publications
7
80
0
2
Order By: Relevance
“…This is in line with our results of increased hepatic glycogen contents in the PBM treated group which showed less fatigue. Constant and high-intensity labor results in the accumulation of metabolites in the body and is the main cause of physical fatigue [41]. In our ndings, forced swimming time signi cantly increased with PBM in female mice indicating they were less fatigued.…”
Section: Discussionsupporting
confidence: 44%
“…This is in line with our results of increased hepatic glycogen contents in the PBM treated group which showed less fatigue. Constant and high-intensity labor results in the accumulation of metabolites in the body and is the main cause of physical fatigue [41]. In our ndings, forced swimming time signi cantly increased with PBM in female mice indicating they were less fatigued.…”
Section: Discussionsupporting
confidence: 44%
“…Identification of GOP were showed that 95.42% of the GOP sample had a molecular weight between 180 and 1000 Dalton. Amino acids accounted for 3.94% [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ginsenoside and polysaccharides are currently the most studied. Meanwhile, ginseng oligopeptides (GOPs) are a kind of nutrients with low molecular weight, high bioavailability, and absorption features, which have numerous potential physiological functions [ 19 , 20 ]. However, studies on the beneficial effects of ginseng oligopeptides (GOPs) on glycemia are rarely conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Điều trị bằng thuốc chống rối loạn lo âu, trầm cảm làm tăng số lần chuyển tiếp giữa hai ngăn, mà không làm thay đổi sở thích của chuột dành nhiều thời gian hơn vào khoang tối . Sự gia tăng hoạt động thăm dò này được giải thích như một sự ức chế khám phá [9][10][11][12][13][14][15][16]. Kết quả ở bảng 4, 5 cho thấy hồng sâm Hàn Quốc liều 200 mg/kg và sâm Ngọc Linh liều 200mg/kg làm tăng đáng kể thời gian lưu của chuột trong buồng sáng (p<0,001) còn ở liều 100 mg/kg, 300 mg/kg sâm Ngọc Linh không làm thay đổi rõ rệt thời gian và số lần lưu của chuột trong buồng sáng so với chứng (p>0,05).…”
Section: Tác Dụng Của Sâm Ngọc Linh Trên Thí Nghiệm Dark/lightunclassified